Factors Contributing to Child Marriage Among Syrian Refugees in Domiz Camp-Kurdistan-Iraq - Qahar, Jabbar Abdulrahman; Hillaluddin, Azlin Hilma; Ahmad Ramli, Fatimah Zailly (Universiti Utara Malaysia Press, 2024)
Child marriage is an internationally recognised human rights issue that has been extensively studied by various Non-Governmental Organisations and the United Nations. In response to this problem, many countries have implemented social policies aimed at addressing child marriage and several international treaties are dedicated to combatting it. This study focuses on examining the factors contributing to child marriage within refugee populations. The research methodology involved conducting in-depth interviews with ten young wives aged between 16 and 22, facilitating focus group discussions with their husbands and parents residing in Domiz Camps 1 and 2 in Kurdistan, as well as interviewing key informants who work in child protection services and social policy development. Thematic analysis was employed to identify prominent themes and subthemes based on the perspectives of participants. The research revealed that child marriage is driven by factors such as the need for safety, preservation of family honour, and economic challenges. Similar safety concerns were observed among Syrian refugees in this study, as well as in previous studies conducted on Jordanian refugees and Rohingya refugees in Bangladesh. This study takes a comprehensive approach by considering perspectives from young wives, their parents, husbands, and key informants when examining factors related to child marriage. Ultimately, the findings of this study will contribute to a deeper understanding of refugee issues and efforts towards protecting children’s rights within the refugee context